Whole body biomechanical differences between limbs exist 9 months after ACL reconstruction across jump/landing tasks - King, E.; Richter, C.; Franklyn-Miller, A.; Daniels, K.; Wadey, R.; Moran, R.; Strike, S. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Previous studies examining jump tasks after anterior cruciate ligament reconstruction (ACLR) have focused on performance measures without examining joint kinematic and kinetic variables. The aim of this study was to identify differences in biomechanical and performance measures between limbs across tests nine months after surgery. Methods